Uji Tuntas Hukum Pengadaan Tanah untuk Kepentingan Umum: Sebuah Tinjauan Kritis - Z. Zainuddin (CV. Social Politic Genius (SIGn), 2022)
This study aims to examine and analyze the legal due diligence approach to land acquisition for the public interest. In addition, to analyze aspects of legal due diligence as a preventive effort to minimize land acquisition problems. This research was conducted using a normative juridical approach with analytical descriptive specifications. The literature study was used to obtain the legal materials needed in this research. The collected legal materials are then analyzed using a qualitative descriptive analysis method. The results show that legal due diligence of land acquisition for the public interest has several objectives: obtaining legal status or legal clarity regarding land documents; checking the validity of the right of ownership to land; checking the legal compliance of land rights owners; providing an opinion for legal certainty of a policy taken by the Government. Furthermore, legal due diligence as a preventive effort to minimize land acquisition problems include: information and data must be valid, comprehensive, and objective; the transaction must be carried out in good faith; investigation and evaluate facts on relevant land objects based on research analysis. Therefore, it is recommended that the Government implement legal due diligence of land acquisition for the public interest as a preventive effort to suppress and minimize the risk of potential legal remedies such as lawsuits that will arise in the future.